From quarks to black holes : interviewing the universe - Hammond, Richard T. (World Scientific, 2001)
This book presents a series of delightful interviews in which natural objects such as an electron, a black hole, a galaxy, and even the vacuum itself, reveal their innermost secrets - not only what they are but also how they feel. A hydrogen atom tells us about quantum mechanics and why we live in a non-deterministic world; a black hole explains curved space and naked singularities; and a uranium atom talks of its life on a meteor, its tremendous collision with Earth, and properties of radioactivity - all while grappling with its own mortality. A neutron star gives a personal account of its creation and goes on to discuss quasars and other extraordinary astronomical objects, while an iron atom describes its birth in a remote supernova explosion and its series of adventures on Earth, from its early use in wrought iron processes to its time in a human body, and then to its latest misadventures. The book discusses many fundamental issues in physics and, at times, examines the philosophical and moral issues of society. For example, the interview with the quark reveals the nature of color gauge symmetry, which is interwoven with a discussion on truth and beauty, and shows how these concepts play an integral part in physics and nature, while the uranium atom expresses its horror of the development and use of the atomic bomb.